We need no wings : a novel - Cardinal, Ann Dávila (Sourcebooks Landmark, 2024)
"To be free, we must learn to fly. Tere Sanchez has always known who she was: a professor, a wife, a mother, and a friend. But when her husband dies unexpectedly, she finds herself completely broken. Taking a leave from the university, Tere hopes that she can mourn her husband and get back on her feet, but instead, she spends a year consumed by grief. Until the day she levitates. Suddenly, Tere's life is thrown into disarray, and the repeated incidents of levitation not only make her question her sanity, but also put her in danger. She decides she will do anything to stop them. So when she's reminded that her family is related to the renowned levitating mystic, Saint Teresa of Avila, she leaves the refuge of her home and travels to Spain, hoping to find answers. But Saints can be elusive, and not all answers are easily found. Tere will soon have to decide whether to remain shrouded in her grief, or open her heart to a world where we need no wings to fly... From the award-winning author of The Storyteller's Death comes a riveting, multicultural story about what it means to love, heal, and take flight"--